Are the Sanctified Becoming the Pornified? Religious Conservatism, Commitment, and Pornography Use, 1984–2016*. (3rd September 2018) - Perry, Samuel L.; Schleifer, Cyrus
Abstract : Objectives: Americans are generally increasing in their pornography viewership. While devout, theologically conservative Christians have been among the most ardent opponents to pornography's dissemination and use historically, there is a growing—but thus far untested—assumption that they too are following this same trend. This study examines (1) whether committed or conservative Christians are increasing in rates of porn viewership similar to other Americans and (2) when potential religious divergences in porn viewership started. Methods: We fit a series of binary logistic regression models using data from the 1984–2016 General Social Surveys. Results: Holding other variables constant, American evangelicals are indeed increasing in their reported porn viewership at rates identical to other Americans. Frequent church attendees and biblical literalists, however, show a divergent trend, with both remaining constant in their reported porn viewership across time. Analyses also show clear cutoff points for the divergence starting in the mid‐1990s, roughly when Internet pornography became available. Conclusions: Findings suggest that, all else being equal, Americans who merely identify with conservative Christianity are indeed increasing in their porn viewership, but among the most faithful and theologically conservative Americans, they are no more likely to report viewing pornography than they were over 30 years ago.